PENGARUH FEE AUDIT DAN ROTASI AUDITOR TERHADAP KUALITAS AUDIT DENGAN KOMITE AUDIT SEBAGAI PEMODERASI - Samantha, Pricillia; Estrini, Dwi Hayu (Universitas Sarjanawiyata Tamansiswa, 2024)
This research aims to determine the effect of audit fees and auditor rotation on the audit quality of the audit committee as a moderator. The population of this study are insurance sector companies that are listed and include financial reports and audit fees on the IDX for 2018-2022. The data used is secondary data from annual reports and audit reports obtained from the BEI website (www.idx.co.id). The data analysis method uses descriptive statistical techniques and classical assumption tests. The research results prove that the audit fee variable has an effect on audit quality and auditor rotation has no effect on audit quality. Meanwhile, the audit committee is able to moderate all independent variables.